Chemical synthesis of the novel Ca2+ messenger NAADP. - Dowden, J; Brown, R; Moreau, C; Galione, A; Potter, B (2005)
The first total chemical synthesis of nicotinamide adenine dinucleotide phosphate (beta-NADP, 2) as a single isomer was achieved. This was subsequently converted into the important second messenger nicotinic acid adenine dinucleotide phosphate (p-NAADP) 1 and the identity of this material confirmed by biological evaluation. This flexible synthetic route offers new opportunities for the generation of NAADP 1 analogues that cannot be generated directly from NADP 2 or mainly enzymatic methods.